Evaluation of the effectiveness of training and development strategies in the mining sector: a case of Zimplats - Manyika, Esther F. (Midlands State University, 2015)
The company is trying to minimise accidents (to achieve zero harm tolerance) at the same time increasing the productivity. The study investigated the effectiveness of training and development programs by the company. The main aim was to establish how the training and development strategies are being implemented and how the training programs are run, establish whether they are being highly effective or not.Explanatory research method was adopted questionnaires and interviews were used to collect primary data, financial statements, books and other online documents were used as secondary data. The total response rate for the whole study was 84%. Tables were used to present and analyse data, responses were coded descriptive statistics with valid percentage were obtained and a chi-square test was run.The major findings in this study were that the training and development strategies were not being highly effective for the company to be able to reach the full production ans zero harm tolerance. Respondents felt that the training programs were not being effectively conducted since majority of them could not highly benefit from the same.The key recommendations in this study are that the company should communicate well the training objectives to the trainees, improve the introduction of training generally improve the design and implementation of their training programs and employers be supportive of training. The study was a cross-sectional study.